2011
DOI: 10.1590/s0102-311x2011000500018
|View full text |Cite
|
Sign up to set email alerts
|

Anemia em crianças de 6 a 59 meses e fatores associados no Município de Jordão, Estado do Acre, Brasil

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
14
0
20

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 31 publications
4
14
0
20
Order By: Relevance
“…This result is similar to those found by other researchers [7,11,13,14,27]. Oliveira et al [27] assessed the prevalence of anemia and its associated factors in children 6-59 months in the state of Pernambuco and found that the children whose mothers had less than 4 years of schooling were more than twice as likely to be anemic.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…This result is similar to those found by other researchers [7,11,13,14,27]. Oliveira et al [27] assessed the prevalence of anemia and its associated factors in children 6-59 months in the state of Pernambuco and found that the children whose mothers had less than 4 years of schooling were more than twice as likely to be anemic.…”
supporting
confidence: 86%
“…This result is similar to those found by other researchers [7,11,13,14,27]. Oliveira et al [27] assessed the prevalence of anemia and its associated factors in children 6-59 months in the state of Pernambuco and found that the children whose mothers had less than 4 years of schooling were more than twice as likely to be anemic. Tympa-Psirropoulou et al [11] investigated the prevalence of anemia in children aged 12-24 months in Greece and found that parents' education affected the presence of anemia in children; the number of cases of anemia was higher among children whose parents had only primary or secondary education.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…A mesma explicação poderia ser atribuída ao maior risco de anemia nas crianças de 6-23 meses que residiam na área rural no ano de 2006, em contraste com crianças de 24-59 meses, grupo que apresentou maior diminuição da prevalên-cia de anemia. O estudo realizado no Município de Jordão, no Acre, é particularmente elucidativo, observando-se 37,5% de anemia nas crianças com ascendência indígena da área urbana e uma prevalência bastante superior (64,3%) nas crianças da área rural 26 . Já a Pesquisa Nacional de Demografia e Saúde de 2006 (PNDS/2006) constatou uma relação estatística bem diferente, observando-se que as crianças de áreas rurais apresentaram uma menor prevalência de anemia quando comparadas às crianças de áreas urbanas 27 .…”
Section: Introductionunclassified